Notary Role in the Implementation of The Cooperation Agreement Between Housing Developers and Land Owner - Rahmatika Nur Hidayah; Akhmad Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
Housing development cooperation between housing developers and owners of land to do to overcome the limitations of the amount of land and pressing capital needs. Generally in this cooperation landowners who provide land, while housing developers set aside, build housing and market it. But such cooperation is prone to risks for both sides, which could lead to disputes or disputes. Notary public officials in law is expected to help prevent the occurrence of the dispute or the dispute. Therefore, the authors are interested in conducting research on the issue, with the aim to determine the role of the Notary in the implementation of the cooperation agreement between the developer residential housing development and land owners. The study was conducted through library research using descriptive method by collecting data, collate, analyze and interpret. In conclusion, as follows: First, the legality of which is clean and clear (CnC) is a very important factor in running the housing business. Second, the need for good faith from housing developers and landowners in implementing the cooperation agreement. Third, the Notary's role is very important in helping to prevent the risk of dispute or disputes by providing legal counseling and make a deed of agreement to provide legal certainty for housing developers and landowners.Keywords: Notary Role; Cooperation Agreement; Developer and Land Owner.